2017
DOI: 10.1039/c7ra00784a
|View full text |Cite
|
Sign up to set email alerts
|

Morphology effects on singlet oxygen production and bacterial photoinactivation efficiency by different silica-protoporphyrin IX nanocomposites

Abstract: Different silica-protoporphyrin IX (PpIX) nanocomposites have been synthesized to evaluate the dependence of singlet oxygen production and bacterial inactivation efficiency on the morphology of the nanomaterials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…It is worth recalling that recently it has been reported that samples similar to those under investigation are photosensitizing the formation of singlet oxygen, which has been quantified by directly monitoring its phosphorescence . These data support the hypothesis that even in the present experimental conditions the samples sensitize the formation of single oxygen; since an indirect method of monitoring ROS formation has been used in the present work, for correctness we will continue to refer generally to reactive oxygen species.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…It is worth recalling that recently it has been reported that samples similar to those under investigation are photosensitizing the formation of singlet oxygen, which has been quantified by directly monitoring its phosphorescence . These data support the hypothesis that even in the present experimental conditions the samples sensitize the formation of single oxygen; since an indirect method of monitoring ROS formation has been used in the present work, for correctness we will continue to refer generally to reactive oxygen species.…”
Section: Resultssupporting
confidence: 84%
“…It has been recently reported that PpIX can be chemically adsorbed on mesoporous silica nanoparticles to minimize the aggregation and assist singlet‐oxygen delivery in aqueous media . Indeed, the morphology and size of pores on the silica surface have been found beneficial for the distribution of PpIX in its monomeric form . However, the porosity of the nanoparticles plays a pivotal role on the singlet‐oxygen production but also on its release from the nanoparticles and delivery to the target cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under dark conditions, porphyrins do not exhibit significant cyto‐ or genotoxicity (Donnelly et al ). Until now applications for porphyrins were essentially performed on cancer cells for photodynamic therapy or on microorganisms as antimicrobial agents (Pläetzer et al , Maish , Pérez‐Lagunal et al , Zampini et al ). For example, upon illumination, protoporphyrin IX and other derivatives induced a strong cytotoxic effect in yeasts Saccharomyces cerevisiae and Candida albicans (Carré et al , Donnelly et al , Cormick et al , Funes et al , Quiroga et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Latterini and co‐workers prepared different silica‐protoporphyrin IX (PpIX) derivatives as antimicrobial agents . The systems—compact silica nanoparticles (CSNP), mesoporous silica nanoparticles (MPSAm), stellate mesoporous silica nanoparticles (MPSSt), and larger pore mesoporous silica nanoparticles (MPSLP)—functionalized with PpIX were synthesized to evaluate the morphology‐dependence of the nanomaterials in the singlet oxygen production and their bacterial efficiency against S. aureus .…”
Section: Ms In Antibacterial Applicationsmentioning
confidence: 99%